Pengamalan Santriwati dalam Mempraktikkan Ta’awun dan Ketakwaan Menurut Kitab Riyadhus Shalihin di Pesantren Salman Alfarisi Binjai Kota - Salsabila Amalia; Rahmi Utami (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2026)
This study aims to analyze the practice of students in implementing the teachings of Riyadhus Shalihin, particularly "Cooperation and Piety," at Pesantren Salman Alfarisi Binjai City. The approach used is descriptive qualitative with data collection techniques through observation and interviews. The results of the study indicate that the value of helping each other (Ta’awun) has been practically implemented in the daily life of the students, whether in learning activities, worship, or social activities within the pesantren environment. The students show attitudes of helping each other in understanding lessons, maintaining cleanliness, and supporting friends who are experiencing difficulties. The value of piety is reflected in discipline in carrying out worship and obedience to pesantren rules. In addition, habituation and the exemplary behavior of the ustazah play an important role in shaping the character of the students. However, there are some obstacles such as differences in the level of understanding and individual awareness that affect the consistency of practice. Overall, the practice of the teachings in this chapter has gone well and has made a positive contribution in shaping noble character, solidarity, as well as a harmonious and religious pesantren environment. This research is expected to serve as a reference in strengthening character education based on Islamic values in pesantren.